Synthesis of Furfural from D-Xylose and Corncob with Chromium Chloride as Catalyst in Biphasic System - Zhang, Ye; Chen, Mingqiang; Wang, Jun; Hu, Qingsong (Asian Journal of Chemistry, 2014)
An efficient process was developed for the conversion of D-xylose into furfural with chromium chloride as catalyst in a biphasic system. The optimal furfural yield of 38.76 % was obtained in the following reaction conditions: reaction temperature 140 ºC, reaction time 1 h and the catalyst loading 2 mmol. Sodium chloride used as co-catalyst was found to affect the furfural yield. A higher furfural yield of 52.55 % was achieved in the presence of 3 g of sodium chloride when using chromium chloride catalyst for the dehydration of D-xylose into furfural. The CrCl3·6H2O-NaCl catalytic system could be recycled and its stable activity was showed after three successive runs. Moreover, this work also provided useful information for the production of furfural from biomass. The furfural yield of 23.88 % was achieved when corncob used as starting materials.